2023
DOI: 10.1371/journal.pone.0286748
|View full text |Cite
|
Sign up to set email alerts
|

Cover cropping impacts on soil water and carbon in dryland cropping system

Abstract: Incorporating cover crops into the rotation is a practice applied across many parts of the globe to enhance soil biological activities. In dryland farming, where crop production is highly dependent on rainfall and soil water storage, cover cropping can affect soil water, yet its effects on soil hydrological and biological health require further investigation. The objective of this study was to evaluate the effect of different timing of summer sorghum cover crop termination on soil water, total and labile organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…Moore et al [17] found that different treatments of cover crop mulches did not affect the yield of subsequently grown soybean when weeds were not present. However, one noted exception was at a location with a high weed presence, which showed a yield increase associated with cover crops due to diminished weed pressure in those plots [13]. Williams II et al [18] found that when soybean stands were not reduced by the implementation of cover crops, the soybean yield were not diminished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moore et al [17] found that different treatments of cover crop mulches did not affect the yield of subsequently grown soybean when weeds were not present. However, one noted exception was at a location with a high weed presence, which showed a yield increase associated with cover crops due to diminished weed pressure in those plots [13]. Williams II et al [18] found that when soybean stands were not reduced by the implementation of cover crops, the soybean yield were not diminished.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Unger et al [12] found that when implemented and managed properly for the promotion of greater water infiltration and reduction in evaporation, subsequent crop yields can be improved. Zhang et al [13] highlighted that moisture dynamics under cover crop systems in dryland settings were all dependent on the management of cover crops. If terminated early, moisture efficiency can be as good as or improved compared to fallow systems.…”
Section: Introductionmentioning
confidence: 99%
“…The cover crop also helps alleviate prolonged droughts during winter and spring in the Weibei Plateau. It allows for the cross-seasonal use of soil water and improves soil water use efficiency [33]. Both the application of organic fertilizer and cover significantly increase SOC and MBC.…”
Section: Effects Of Cover Crop and Fertilizer Management On Soil Phys...mentioning
confidence: 99%